Strategi Guru dalam Meningkatkan Mutu Pembelajaran PAI melalui Pemanfaatan Teknologi - Okta Rosfiani; Cecep Maman Hermawan; Devanita Novia Ardana; Hizrian Nugraha; Denis Ramadhan; Rihadatu Alifia (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This qualitative phenomenological study aims to explore strategies, supporting-inhibiting factors, and the impact of technology utilization by Islamic Religious Education (PAI) teachers in improving the quality of learning. Data were collected through in-depth interviews with selected PAI teachers and grade 8 students, participant observation of learning, and document analysis (RPP, digital content), the data was then analyzed using thematic analysis. The main supporting factors include the development of Technological Pedagogical Content Knowledge (TPACK) through the PAI Subject Teacher Deliberation (MGMP) and school policy support, while crucial obstacles include infrastructure gaps, student resistance, and ethical dilemmas in the use of AI. The use of technology has a holistic impact on the quality of learning 1) Increased student participation (40%) and critical engagement; 2) Strengthening cognitive understanding (+35% digital ethics analysis) and character (noble morals) (Mulyasa, 2021). This study contributes theoretically through the development of an Islamic values-integrated TPACK model and practically in the form of strategy recommendations for teachers, Islamic Education-specific TPACK training policies for teachers, and the development of sharia-compliant educational applications. The main conclusion confirms that the effectiveness of technology in Islamic Education depends on creative adaptations that synergize pedagogy, Islamic content, and socio-technical contexts.